Fructans with Varying Degree of Polymerization Enhance the Selective Growth of Bifidobacterium animalis subsp. lactis BB-12 in the Human Gut Microbiome In Vitro - Pieter Van den Abbeele; Cindy Duysburgh; Jonas Ghyselinck; Shellen Goltz; Yulia Berezhnaya; Thomas Boileau; Anke De Blaiser; Massimo Marzorati (Applied Sciences, 2021)
Synbiotics aim to improve gastrointestinal health by combining pre- and probiotics. This study evaluated combinations of Bifidobacterium animalis subsp. lactis BB-12 with seven fructans: oligofructoses (OF1-OF2; low degree of polymerization (DP)), inulins (IN1-IN2-IN3; high DP) and OF/IN mixtures (OF/IN1-OF/IN2). During monoculture incubations, all fructans were fermented by BB-12 as followed from increased BB-12 numbers and increased acetate and lactate concentrations, with most pronounced fermentation for low DP fructans (OF1-OF2). Further, short-term colonic incubations for three human donors revealed that also in presence of a complex microbiota, all fructans (particularly OF1) consistently selectively enhanced the growth of BB-12. While each fructan as such already increased Bifidobacteriaceae numbers with 0.94–1.26 log(cells/mL), BB-12 co-supplementation additionally increased Bifidobacteriaceae with 0.17–0.46 log(cells/mL). Further, when co-supplemented with fructans, BB-12 decreased Enterobacteriaceae numbers (significant except for IN1-IN3). At metabolic level, all fructans decreased pH due to increased acetate and lactate production, while OF/IN2-IN1-IN2-IN3 also stimulated propionate and butyrate production. BB-12 co-supplementation further increased propionate and butyrate for OF/IN2-IN3 and IN1-IN2, respectively. Overall, combinations of BB-12 with fructans are promising synbiotic concepts, likely due to intracellular consumption of low DP-fructans by BB-12 (either present in starting product or released upon fermentation by indigenous microbes), thereby enhancing effects of the co-administered fructan.